Learning in an exotic social wasp while relocating a food source - Lozada, Mariana (2014)
In this paper we review several studies on V. germanica behavioral plasticity while relocating a food source in natural environments. This exotic social wasp, which has become established in many parts of the world, displays diverse cognitive abilities when foraging. Given its successful invasiveness worldwide, our initial hypothesis was that this species has great behavioral plasticity, which enables it to face environmental uncertainty. In our work we have analyzed foraging behavior associated with undepleted resources. Throughout several experiments, rapid learning was observed in this species; after few learning experiences they associate diverse contextual cues with a food source. However, by exploring wasp behavior when food suddenly disappeared, either because it had been removed or displaced, we found that they continued searching over a no longer rewarding site for a considerable period of time, suggesting that past experience can hinder new learning. Particularly surprising is the fact that when food was displaced nearby, wasps persisted in searching over the empty dish, ignoring the presence of food close by. We propose that this species could be a suitable model for studying cognitive plasticity in relation to environmental uncertainty.